UTILIZATION OF NETWORK-BASED LEARNING TECHNOLOGY BY MILLENNIAL GENERATION LECTURERS: A REVIEW OF ARABIC LANGUAGE LEARNING IN HIGHER EDUCATION - Nukman, Nukman; Hidayat, Ahmad Fadhel Syakir (STIQ Amuntai, 2024)
It is a major topic among academics that the supporting factor for introducing technology to Generation Z in Arabic language learning is the lecturers, mostly filled by the Millennial generation. Therefore, this study aims to explore the utilization of network-based technology by millennial generation lecturers (a review of Arabic language learning in higher education). This research is based on post-positivistic paradigm with quasi-qualitative approach; the data collection methods are interviews, observation, and documentation. The research subjects were 29 millennial generation lecturers born between 1981 and 1996. The data analysis technique used the analysis Miles, Huberman, and Saldana. The results of this study are face-to-face direct feedback-based material delivery technology by millennial lecturers relying on Zoom and Google Meet. In contrast, non-face-to-face direct feedback-based material delivery technology, WhatsApp, and Telegram are still the main applications. As for the technology of providing material based on indirect feedback on the audio aspect, there is no visible use of certain platforms or applications on them; on the audio-visual aspect, millennial lecturers actively create video content on the YouTube platform, while on the text aspect, the use of WordPress, Blogger or special websites is a separate choice for some millennial lecturers. Evaluation technology: several platforms are the choice of millennial lecturers, including Google Form, Quizizz, Kahoot, Quizlet, and Wizer.me. As for special platforms designed for learning purposes, each lecturer still relies on e-learning provided by their respective education units. However, there is an e-learning that is the first choice of most millennial lecturers, namely Moodle.